A Performant State-of-Art Tool to Assess Cross-Border Impact of Industrial Activities. A Transboundary Air Pollution Case Study. (2016) - Popescu, Francisc
Abstract: The paper focus is on the air pollution episode generated by a closed mining tailings dump located on Danube banks in historical Banat region, between Romania and Serbia. In this paper a new generation Gaussian plume air dispersion model was used, based on the hypothesis that the atmospheric boundary layer properties are characterized by the boundary layer depth and the Monin-Obukhov length rather than in terms of the single parameter Pasquill-Gifford class. The case-study focuses on a sensible case of Romania-Serbia cross-border case generated by the lack of maintenance of a closed mining tailings dump and the evaluation of an area type pollution source on the surrounding environment.